Anti-Neuronal Autoantibodies (Cell Surface and Onconeural) and Their Association With Natural Autoantibodies in Synthetic Cannabinoid-Induced Psychosis - Hau, Lídia; Tényi, Tamás; László, Natália; Kovács, Márton Áron; Erdö-Bonyár, Szabina; Csizmadia, Zsuzsanna; Berki, Tímea; Simon, Diána; Csábi, Györgyi (Frontiers in Psychiatry, 2022)
Patients suffering from encephalitis may present psychiatric symptoms, however the clinical relevance of anti-neuronal antibodies in patients experiencing a psychotic episode without encephalitis is still unclear. In this study we examined the presence of anti-neuronal cell surface autoantibodies and onconeural autoantibodies in serum samples of 22 synthetic cannabinoid users presenting with psychosis. We found only 2 positive cases, however, 7 patients had borderline results. Nonetheless, we found no significant correlation between anti-neuronal autoantibodies and the intensity of psychosis indicated by the Positive and Negative Syndrome Scale (PANSS) scores. The length of drug use and the combination of other drugs with synthetic cannabinoids had no significant effect on anti-neuronal autoantibody positivity. Nonetheless, the ratio of anti-citrate synthase (anti-CS) IgM and IgG natural autoantibodies was significantly lower (p=0.036) in the anti-neuronal autoantibody positive/borderline samples, than in the negative group. Interestingly, anti-CS IgM/IgG showed a significant negative correlation with PANSS-positive score (p=0.04, r=-0.464). Our results demonstrated that anti-neuronal autoantibody positivity occurs in synthetic cannabinoid users, and the alteration of anti-CS IgM/IgG natural autoantibody levels points to immunological dysfunctions in these cases.